Contribuições ao estudo de conexão de geração eólica à rede elétrica - Jaskulski, Igor Weide (2007)
Distribution systems have not been designed to receive distributed generation (DG) units. The electric energy injection in these systems is safe and reliable if the characteristics regarding of DG interconnection in distribution power systems are considered: (i) Protection; (ii) Stability; (iii) Electric energy market; (iv) Quality of energy. In this work, aspects regarding of quality of energy and protection are studied. In the quality of energy aspect, converters with legs in parallel are approached. To demonstrate the power capability increase with converters with legs in parallel, the capabilities power curves of the converter are derived. Furthermore, a procedure to design an inductive filter from the distortion factor and limits of current harmonics is described. It is shown that converters with legs in parallel can be used to decrease the current harmonic content in the output of the DG and to increase the power curve capability of the converter. In the protection aspect, the stability analysis of an islanding detection method (IDM) based in positive feedback that has not Non-Detection-Zone (NDZ) is shown. A complete and a reduced dynamic model are derived. The results demonstrated that the reduced dynamic model is valid for the proposed analysis. Furthermore, a stable operation of an islanded utility section is demonstrated. However, if the IDM is added in the DG control system, it is possible a stable operation when the main utility is connected and an unstable operation when the DG unity is operating in islanding condition. Besides, the addition of a limiter in the output of the MDI can represent a limit cycle that induces a voltage oscillation in the islanded section that can be useful to under/over voltage relays coordination. Finally, a three phase converter with two legs per phase in parallel is used to validate the analyses.